(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
Apollon Myrikaios in Lesbos and Apollon Koropaios in Korope, both using the tamarisk in divination, were independent from Delphi, but their cult was not less important, at least locally.